Issues of organization of customs audit - Saifullayev Mehrozh Saifullayevich (International Consortium of Education and Culture Research Studies, 2019)
In international practice, a lot of scientific and practical research has been carried out to improve the organization and conduct of customs audits, the development of international standards, the further development of the customs audit process.